Stress and emotion regulation in resident doctors at a tertiary care hospital of North India - Singh, Chitvan; Singh, Udeyana; Soni, Anshu; Verma, Rohit (International Journal of Research in Medical Sciences, 2019)
Background: The stress of medical training stems from academic pressure, exhausting work hours and striving for perfectionist standards. The demanding nature also requires involvement with emotionally draining aspects of life (human suffering, death, sexuality and fear). This may impair quality of life of medical students and influence patient care. As a consequence, post graduate medical students can experience an alarming amount of stress-associated anxiety, depression, substance abuse, and even suicide. Chronic stress is also known to influence memory, learning and especially problem-solving abilities which require flexible thinking. The study was carried out to evaluate the relationship of stress to cognitive reappraisal and emotion suppression in post graduate medical students. Methods: 150 post graduate medical students participated in the study. Emotion Regulation Questionnaire and Professional Life Stress Questionnaire were administered on each participant. Data collected was kept confidential. Results were tabulated and statistically analysed. Results: Out of 150 participants, 85 (56.67%) experienced stress. 65 (43.33%) participants had stress in the moderate range, 20 (13.33%) participants had stress in the problematic area for whom remedial action was required. 52% showed high cognitive reappraisal, while 54% showed emotional suppression. Conclusions: The correlation between stress, cognitive reappraisal and between stress, emotion suppression showed weak strengths.